SUBAK - Mulyati Mulyati (Jantra., 2019)
The Subak ritual ceremony is the implementation of Parhyangan which is an important part of Tri Hita Karana (THT). In this context, Parhyangan presents a harmonious relationship between the farmers and God. The other components of THK are pawongan (the harmonious relationship among Subak members), awig-awig (the implementation of Subak management), and palemahan (harmonious relationship between farmers and the environment by maintaining the rice field terraces). There are 16 activities of ritual ceremonies which are individually performed by a Subak member, starting from taking irrigation water until the post harvest ceremony. This descriptive analytic research collected the data from library research and field observations. The research results show that Subak has been regarded as one of the guards of Balinese culture. It is not surprising that UNESCO has acknowledged Subak asworld cultural heritage. Subak are bound by physical and spiritual concerns. The strength of Subak lies in the interdependence of its members on irrigation water and they are united by the existence of the Subak Temple.